Susceptibility profile of Zimbabwean livestock fecal Escherichia coli isolates to veterinary antibiotics: Implications for standardization of antimicrobial resistance surveillance in livestock production - Anderson Munengwa; Chikumba Nation; Mugoti Alban; Dziwanyika Lenin (Aceh Journal of Animal Science, 2022)
Susceptibility patterns of Escherichia coli to Veterinary Critically Important Antimicrobials (VCIAs) are poorly understood in most developing countries. We determined those patterns on n = 180 livestock fecal isolates from Chikomba district by disk diffusion method. Multiple Antibiotic Resistance (MAR) indices for the isolates were determined for risk analysis. Chi-square was used to test how antibiotic susceptibility level associated with animal species and farming scale. Resistance to Tetracycline and Ampicillin was high across animal species (above 70%). Moderate levels of resistance (30% to 54%) to Erythromycin, Trimethoprim and Chloramphenicol were detected across livestock species. Resistance levels were low (below 30 %) for Ciprofloxacin and Gentamicin. Resistance to Gentamicin, Tetracycline, Ciprofloxacin, Ampicillin, Chloramphenicol and Ceftazidime was associated with animal species (P ˂ 0.05). Antibiotic susceptibility patterns were independent of farming scale (P 0.05). Frequencies of isolates within each risk zone depended on animal species (P ˂ 0.05), contrary to farming systems (P 0.05). Multi-Drug Resistance was 73%, where most isolates were resistant to 5 antibiotics (23%) and none exhibited resistance to all antibiotics. Only 55% of isolates from cattle and over 80% from pigs and layers were within the high risk zone.  Twenty nine of the isolates were extended spectrum beta lactamase (ESBL) positive. Higher ESBL frequencies (44%) were observed within Large Scale Commercial Farms (LSCF) followed by for Small Scale Commercial Farms (SSCF) (25%) and Resettlement farms (A1) (14%). Similarly, ESBL prevalence varied by livestock species (P 0.05), as follows: pig (39%), layers (32%) and beef (12%). Our study suggests high incidences of multi-drug resistance in livestock which need AMR surveillance strategies. Keywords: Antibiotic resistance, Pigs, Poultry, Beef cattle, Escherichia coli